Alcune lettere inedite della legazione di Baldassarre Carducci alla corte di Francesco I (1529-1530) - Alessandro Monti (Laboratoire Italien)
Between 1529 and 1530 Florence was besieged by the army of Charles Vth. During the same period the florentine ambassador Baldassarre Carducci was engaged in a diplomatic mission in France, at the court of Francis Ist. Excluding the documents already published in the nineteenth century by Desjardins and Canestrini, the Carducci’s mission is largely unknown, and particularly obscure are the letters sent to Florence during the months of the siege. In those months Carducci insistently asked to Francis Ist for a military or economic aid to the tuscan city. The author presents in this article six unpublished letters, recently found in the Archivio di Stato di Firenze, useful to explain the background of relations between France and Florence in the last months of life of the Florentine Republic.